Novel Case of Prader–Willi Syndrome and Ebstein's Anomaly: Implications for Complex Care Management - Mattia, Donald; Lindblade, Christopher; Oatman, Oliver; Prakash, Supraja; Grebe, Theresa (Journal of Pediatric Genetics, 2022)
We present a patient with a complex phenotype including diagnoses of Ebstein's anomaly and Prader–Willi syndrome (PWS) as well as additional congenital anomalies and genetic variants with potential clinical effects. This is the first reported case of both diagnoses present in the same patient. The diagnosis of Ebstein's anomaly was made on prenatal ultrasound. She presented with neonatal hypotonia, feeding problems, and dysmorphic features, followed by later onset weight gain, leading to a diagnosis of PWS. Further evaluations revealed Blaschkoid hyperpigmentation, laryngeal cleft, and pigmentary retinopathy. Whole exome sequencing determined a likely pathogenic variant in alkaline phosphatase gene and several mitochondrial DNA variants. We discuss the known genetic mechanisms of PWS and compare them to the heterogenous genetic associations of Ebstein's anomaly. The standard of care treatment for PWS is growth hormone therapy, which is associated with right-sided heart failure risks. This case illustrates the need to complete the diagnostic work up in all patients, as well as the necessity of a multidisciplinary approach for optimal outcomes.
Keywords: Prader–Willi; Ebstein's anomaly; Growth hormone; Blaschkoid hyperpigmentation